2016
DOI: 10.1007/s40615-016-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Place Matters in Non-Traditional Migration Areas: Exploring Barriers to Healthcare for Latino Immigrants by Region, Neighborhood, and Community Health Center

Abstract: This paper identifies differences in adult Latino immigrant barriers to healthcare in the Cincinnati area in Hamilton County, OH on three levels: by region, by neighborhood, and by community health center. Secondary data analysis was performed on 439 surveys. Respondents were aggregated by the geographic regions and neighborhoods where they live and by two community health centers where they receive care. Outcome measures included pragmatic and skill barrier indices adapted from the Barriers to Care Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…We observed that minorities, low‐income adults, and those with public or no health insurance were more likely to delay care due to lack of transportation compared to white adults even when adjusted for other possible confounding factors. This is similar to well‐established findings throughout the medical literature that minorities, low‐income individuals, or those with inadequate health insurance face higher barriers to healthcare and encounter issues related to transportation to appointments and missing work . For example, geographic analysis of women with breast cancer in Atlanta revealed a significantly longer commute via public transportation to the nearest radiation therapy facility for black women compared with white women .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We observed that minorities, low‐income adults, and those with public or no health insurance were more likely to delay care due to lack of transportation compared to white adults even when adjusted for other possible confounding factors. This is similar to well‐established findings throughout the medical literature that minorities, low‐income individuals, or those with inadequate health insurance face higher barriers to healthcare and encounter issues related to transportation to appointments and missing work . For example, geographic analysis of women with breast cancer in Atlanta revealed a significantly longer commute via public transportation to the nearest radiation therapy facility for black women compared with white women .…”
Section: Discussionsupporting
confidence: 84%
“…For example, geographic analysis of women with breast cancer in Atlanta revealed a significantly longer commute via public transportation to the nearest radiation therapy facility for black women compared with white women . Low‐income individuals and minorities are more likely to live in neighborhoods that are isolated from healthcare facilities and lack sufficient healthcare resources . Inadequate health insurance is also a factor in geographically limiting where care for voice problems can be received, which likely leads to having to travel farther to obtain voice services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilising a peer model also has benefits and advantages for the peer communities including actionable project findings/results applicable to the community, improved health and social services, enhanced understanding of community needs and priorities and increased awareness of important issues at community level, social change and justice (Baynes et al., ; Boise et al., ; Brown et al., ; Calhoun, ; Chen et al., ; Cortez et al., ; Dill, ; Downey et al., ; Gabriel et al., ). Furthermore, working with peers in a peer model can improve the quality of research, education and interventions in terms of recruitment, contextually and culturally relevant questionnaires, methods and techniques, data collection and screening, interpretation of results and translation and dissemination of findings (Chang et al., ; Horowitz, Brenner, Lachapelle, Amara, & Arniella, ; Hull et al., ; Martin et al., ; McElfish et al., ; Minkler et al., ; Olsson et al., ; Sharma et al., ; Topmiller, Zhen‐Duan, Jacquez, & Vaughn, ).…”
Section: Discussionmentioning
confidence: 99%